Determination of cardinal temperature of Euphorbia maculata and its hydrothermal model of germination - Shayesteh Salehi; مرجان دیانت; Ghorban Noormohammadi (علوم و فناوری بذر ایران)
In order to quantify the germination characteristics and determine the cardinal temperature of germination of Euphorbia maculata, seeds were placed at constant temperatures (2- 45 °C). Results showed that seed of E.maculata had no germination at temperatures of 2, 5, 10 and 45 ° C, and the temperature of 30° C was the best temperature for germination seeds (91% Germination percentage). Three models of intersected-line, dent-like segmented and quadratic polynomials were used to estimate the cardinal temperatures. The best model for estimating the cardinal temperatures in E.maculata was intersected-line model with respect to coefficient of determination and mean square error. According to the intersected-line the minimum, optimum and maximum temperatures were calculated 9.8, 28.33 and 43.16 °C. In order to investigate water potential on germination percentage, seeds treated with water potentials (0, -0.2, -0.4, -0.6 and -0.8 MPa) at optimum temperature of 28°C. Baesd on the three-parameter sigmoid method, the value of speed, root length, stem length, seedling fresh weight and dry weight were estimated to be -0.53, -0.48, -0.51, -0.48, -0.52Mpa respectively. According to the hydro-time model based on normal distribution, the hydro-time constant and the base-water potential (which is a threshold for germination beginning) of E.maculata degree were 291.32 (MPa/h) and -1/2 (MPa) at 28 °C, respectively. Thus, this weed species has a great potential for distribution to other areas such as provinces with a dryer climate than Golestan, and the necessary measures to prevent its distribution is necessary.